Physiological and Metagenomic Characterizations of the Synergistic Relationships between Ammonia- and Nitrite-Oxidizing Bacteria in Freshwater Nitrification - Cai, Mingwei; Ng, Siu-Kin; Lim, Chee Kent; Lu, Hongyuan; Jia, Yangyang; Lee, Patrick K. H. (Frontiers in Microbiology, 2018)
Nitrification plays a crucial role in global nitrogen cycling and treatment processes. However, the relationships between the nitrifier guilds of ammonia-oxidizing bacteria (AOB) and nitrite-oxidizing bacteria (NOB) are still poorly understood, especially in freshwater habitats. This study examined the physiological interactions between the AOB and NOB present in a freshwater aquarium biofilter by culturing them, either together or separately, in a synthetic medium. Metagenomic and 16S rRNA gene sequencing revealed the presence and the draft genomes of Nitrosomonas-like AOB as well as Nitrobacter-like NOB in the cultures, including the first draft genome of Nitrobacter vulgaris. The nitrifiers exhibited different growth rates with different ammonium (NH4+) or nitrite concentrations (50 to 1,500 μM) and the growth rates were elevated under a high bicarbonate (HCO3-) concentration. The half-saturation constant (Ks for NH4+), the maximum growth rate (μmax), and the lag duration indicated a strong dependence on the synergistic relationships between the two guilds. Overall, the ecophysiological and metagenomic results in this study provided insights into the phylogeny of the key nitrifying players in a freshwater biofilter and showed that interactions between the two nitrifying guilds in a microbial community enhanced nitrification.